Cinema 16 American short films - Davidson, Adam; Sollett, Peter 1976-; Lucas, George 1944-; Burton, Tim; Van Sant, Gus 1952- (Rough Trade, 2006)
The short films included are The Lunch Date, Five Feet High and Rising, Freiheit, Daybreak Express, Vincent, Terminal Bar, Terry Tate: Office Linebacker, Necrology, The Discipline of D. E., The Wraith of Cobble Hill, George Lucas in Love, Meshes of the Afternoon, Carmen, Feelings, Paperboys, and Screen Test: Helmut